Implementation of Identity Based Encryption in e-Voting System - Selamat, S. R.; Yusof, R.; Kong, P. R (2007)
This paper explains about the design and implementation of Identity Based Encryption (IBE) in web-based Voting application. IBE is a completely new approach to the problem of encryption which was found on the traditional Public Key Infrastructure. It can be used on any arbitrary string as a public key, enabling data to be protected without the need for certificates and reduction of infrastructure cost due to certificates database maintenance. Protection implemented in this application is a key server that controls the mapping of identities to decryption keys where the key is only one-time pad implementation. By using the IBE technique, authentication and security can be preserved in the web-based Voting application where it provides integrity, authenticity, anonymity and confidentiality in this application.